Coming home - Ruth, Greg (New York : Feiwel and Friends, 2014)
Follows the emotions of a young boy as he waits at an airport for a family member to return home from serving in the military.
Keywords: Children of military personnel -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Homecoming -- Juvenile fiction; Picture books for children; Children of military personnel -- Fiction; Families of military personnel -- Fiction; Soldiers -- Fiction; Picture books for children; Children of military personnel; Homecoming; Mothers and sons; Fiction; Juvenile works